Optimal wage setting for an export oriented firm under labor taxes and labor mobility - Raúl Ponce Rodríguez (Nóesis)
In this paper it is developed a theoretical model to study the incentives that a labor tax might induce in terms of the optimal wage setting for an export oriented firm. In particular, we analyze the interaction of a labor tax that tends to reduce the wage due the firm is induced to shift backwards the tax burden to its employees minimizing the possible increase in the payroll costs and a fall of profits. However a lower wage might not be an optimal response to the establishment of a labor tax because it increases the labor turnover and as a result the firm faces both: an outputs opportunity cost and a labors turnover cost. The firm thus optimally decides to respond to the qualification and labor taxes by increasing the after tax wage.